The effectiveness of noise interventions in the ICU. Issue 2 (April 2019) - Delaney, Lori; Litton, Edward; Van Haren, Frank
Abstract : Purpose of review: Excessive noise has direct adverse physiological and psychological effects, and may also have indirect negative health consequences by reducing sleep quality and quantity. This review presents a synthesis of the epidemiology of noise in the ICU, and the potential interventions designed to attenuate noise and protect patients. Recent findings: Noise increases cortisol release, oxygen consumption, and vasoconstriction. ICU noise levels are excessive throughout the 24-h cycle, irrespective of level of intervention or whether the patient is in a side room or open ward. Direct measurement suggests that noise is a substantial contributor to poor sleep quantity and quality in the ICU and is frequently recalled by survivors of critical illness as a negative experience of ICU admission. Noise abatement, environmental masking and pharmacological interventions may all reduce the impact of noise on patients. However, the sustainability of behavioural interventions remains uncertain and high-quality evidence demonstrating the benefit of any intervention on patient-centered outcomes is lacking. Summary: Noise levels in the ICU are consistently reported to reach levels likely to have both direct and indirect adverse health consequences for both patients and staff. Noise reduction, abating the transmission of noise and pharmacological modulation of the adverse neural effects of noise are all potentially beneficial strategies, although definitive evidence of improved patient-centered outcomes is lacking.